Chemical, biological, and trophic status of temperate lakes can be strongly influenced by the presence of late-glacial marine sediments. (2nd January 2020) - Norton, Stephen A.; Amirbahman, Aria; Bacon, Linda; Ewing, Holly A.; Novak, Martin; Nurse, Andrea; Retelle, Michael; Stager, J. Curt; Yates, Martin
Abstract: Norton SA, Amirbahman A, Bacon L, Ewing HA, Novak M, Nurse A, Retelle M, Stager JC, Yates M. 2019. Chemical, biological, and trophic status of temperate lakes can be strongly influenced by the presence of late-glacial marine sediments. Lake Reserv Manage. 36:14–30. Lake Auburn, Maine, is a water supply for 60, 000 people. Unusual silt/clay sediment, >4 m thick, occurs 15 cm below gyttja in deep water cores. We characterized cores taken in 2015 and 2016 (57 and 425 cm long, respectively), from 35 m. We determined 137 Cs, 210 Pb, and 206 P/ 204 Pb ratios to establish chronology for the cores and to link them stratigraphically. At least 1.1 m of sediment has accumulated since European settlement due to watershed erosion from land clearance and disturbance from about 1750 onward. The increased lake level from dams established in 1851 and the 1950–1960s has caused shoreline erosion. Extraction of sediment with HCl, scanning electron microscopy, and energy-dispersive spectroscopy analyses confirmed the presence of apatite (Ca5 (PO4 )3 (OH)) for at least the upper 3.5 m of sediment. The apatite is soluble because of the circumneutral pH and relatively low Ca 2+ concentrations. This modern sediment is derived from postglacial marine silt/clay sediment and represents a rarely considered internal source of P that predisposes the lake's water column to higher total P, rendering it more susceptible to episodic eutrophication from stresses including higher temperatures, more frequent high-intensity weather phenomena, and longer ice-free periods with stronger and longer stratification. This previously unrecognized source of P must be considered in water quality management, including chemical mitigation such as aluminum addition, lake level manipulation, and watershed erosion control. Similar situations likely exist in other coastal lakes in postglacial terrain that was inundated during deglaciation, and in inland lakes receiving sediment directly during deglaciation.